2003
DOI: 10.1016/s0736-0266(02)00142-0
|View full text |Cite
|
Sign up to set email alerts
|

The effect of selected growth factors on human anterior cruciate ligament cell interactions with a three‐dimensional collagen‐GAG scaffold

Abstract: Our work focuses on development of a collagen-glycosamimoglycan (CC) scaffold to facilitate ligament healing in the gap between the ruptured ends of the human anterior cruciate ligament (ACL). In the present investigation, we evaluated the effects of selected growth factors on human ACL cell responses important in tissue regeneration, namely cell migration, proliferation, collagen production, and expression of a-smooth muscle actin (SMA).Methods: Explants from six human ACLs were cultured on top of a CG scaffo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 124 publications
(67 citation statements)
references
References 43 publications
3
63
0
Order By: Relevance
“…[19][20][21][22] Cell growth and collagen proliferation were observed in vitro in ACL and MCL cultured with growth factors such as basic fibroblast growth factor (b-FGF), transforming growth factor-b (TGF-b), platelet-derived growth factor (PDGF), and EGF. 10,13 In an in vivo experiment with b-FGF, new vessels invaded injury sites in less time, thereby accelerating the overall healing process.…”
Section: Discussionmentioning
confidence: 99%
“…[19][20][21][22] Cell growth and collagen proliferation were observed in vitro in ACL and MCL cultured with growth factors such as basic fibroblast growth factor (b-FGF), transforming growth factor-b (TGF-b), platelet-derived growth factor (PDGF), and EGF. 10,13 In an in vivo experiment with b-FGF, new vessels invaded injury sites in less time, thereby accelerating the overall healing process.…”
Section: Discussionmentioning
confidence: 99%
“…Again, k is the carrying capacity of the collagen molecules in engineered cartilage constructs (noted as K 2 in the text). The steady state probability density function for GAG accumulation as a fraction of construct carrying capacity under the simulated variability of growth factor (described by equation 20), where λ 1 = 1/187, 36 and ℜ 1 = 0.05. The steady state probability density function for collagen deposition as a fraction of construct carrying capacity under the simulated variability of growth factor (described by equation 21), where λ 2 = 1/18.9, 36 and ℜ 2 = 0.2.…”
Section: Discussionmentioning
confidence: 99%
“…1 Meaney Murray et al 20 observed that a number of selective growth factors could remarkably increase the collagen production in ECM. Both in vivo and in vitro experiments show that some growth factors enhance the production of biomolecules and some inhibit it.…”
Section: Introductionmentioning
confidence: 99%
“…Collagen has found widespread use as a scaffold and carrier for cells in various tissue engineering applications, specifically, soft tissue applications such as skin 16,17 and cartilage. 18,19 Natural carbohydrates have been utilized as hydrogels not only for drug delivery, but also for tissue engineering. 20 Among these, the linear glycosaminoglycan hyaluronic acid (HA), which is composed of repeating disaccharide units of glucuronic acid and N-acetylglucosamine, is widely distributed in the ECM and critical to vertebrate tissue morphogenesis.…”
Section: Polymeric Biomaterialsmentioning
confidence: 99%